Sugarcane Bagasse Ash as a Partial Replacement for Cement in Concrete - Ghosh, Barnali (AMC Indian Journal of Civil Engineering, 2024)
To minimize industrial and agricultural waste, a lot of research is being carried out. Sugarcane bagasse ash (SCBA) is a byproduct of the sugarcane industry. After the juice is taken out from the sugarcane, the remaining part which is known as bagasse is converted to ash under high temperature. This ash has good pozzolanic properties. As conventional materials for concrete is not available easily, the use of local and waste materials has increased significantly. Sugarcane bagasse ash can be a good substitute of cement in concrete due to its significant pozzolanic properties. The main objective of this study is to find the optimum percentage of replacement of sugarcane bagasse ash based on compressive strength and flexural strength of concrete. Thus, the use of sugarcane bagasse ash as a partial replacement of cement in concrete can be a very good alternative to cement and can be very good for the environment. This saving of resources and the management of agricultural waste simultaneously encourages a circular economy in the construction sector.